FUTSAL EXTRACURRICULAR COUNSELING STRATEGY IN IMPROVING STUDENTS' NON-ACADEMIC ACHIEVEMENTS AT SDN 081 PANYABUNGAN - Sri Wahyuni; Muhammad Ismail Marzuki; Riski Padilah; Inri Atikah Rahmadani Lubis (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study aims to describe the futsal extracurricular coaching strategy in improving students' non-academic achievements at SDN 081 Panyabungan. The study used a descriptive qualitative approach with futsal extracurricular coaches and students as research subjects. Data collection techniques were carried out through interviews, observation, and documentation, while data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, with data validity guaranteed through triangulation of sources and techniques. The results of the study indicate that the futsal extracurricular coaching strategy is implemented through short-term and long-term training planning, structured and sustainable coaching implementation, and systematic evaluation. This coaching strategy is able to improve students' non-academic achievements, both in the form of championship achievements and character development such as discipline, self-confidence, teamwork, and sportsmanship. Thus, futsal extracurricular coaching plays a strategic role in developing students' non-academic potential optimally and sustainably.